Degenerative lesion of the vertebral column: a new view of the disease, approaches to therapy (the authors' own findings) - N A Shostak; N G Pravdyuk; N A Shostak; N G Pravdyuk (Современная ревматология)
An open-labeled randomized study of the efficacy and safety of Piascledine-300 in combination with nonsteroidal anti-inflammatory drugs (NSAIDs) versus the latter was conducted in 2 matched groups of patients with lower back pain associated with spondylarthrosis. During combined therapy using Piascledine, there was a reduction in the pain syndrome particularly with the longer administration of the drug. The use of Piascledine in spondylarthrosis showed its clinical efficacy in 89,2% of patients: the indices of lumbago substantially reduced and spinal function improved, which was associated with the good tolerability of the drug.